PERANCANGAN MODEL PEMBELAJARAN TEAMS GAME TOURNAMENT MONOPOLI BUDAYA NTT MENGGUNAKAN GENIALLY - Jhon Enstein; Khatrin Juliani Taku Neno; Femberianus Sunario Tanggur (FKIP Universitas Citra Bangsa, 2022)
This study aims to introduce the cultural diversity of East Nusa Tenggara (NTT) Province through the TGT (Team Game Tournament) NTT cultural monopoly in Elementary School Students of East Nusa Tenggara. This application was designed using the type of research and development (R&D) with the GDLC (Game Development Life Cycle) software development method. There were some stages applied in this research. It was started from Initiation, preproduction, production, Testing (Alpha testing, Beta testing), and release. The NTT Cultural Monopoly Game ran according to its function and it was acceptable to be used by teachers and students. This game increased new concept, new insight and references related to Interactive Learning media. Keywords: Learning Model, Teams Game Tournament, Cultural Monopoly, Game Development Life Cycle, Interactive Learning Media.